N2O Emission from Managed Soil Under Different Crops in Rainfed Area, Central Java - Ariani, Miranti; Hervani, Anggri; Setyanto, Prihasto (JOURNAL OF TROPICAL SOILS, 2016)
N2O emission from agriculture has been assumed to increase by 30-35% until 2030. This gas has a major contribute to the emission from agriculture. N2O emission from managed soils is the 2nd contributor to green house gas (GHG) emission from agriculture in Indonesia. Rainfed area requested high management input. This research aimed to examine N2O emission from different crops in the rainfed area and its affecting factors, also to identify things that need to be considered in conducting N2O measurement from managed soil. Research conducted in Pati and Blora District, Central Java Province. Four (4) different experimental sites with 4 different crops were chosen. Those were mung bean, rubber plantation and sugarcane which located within Pati District, and maize crop which located in Blora District. No treatment was applied. Gas samples were taken following the day after fertilizing. Daily N2O fluxes from managed soil in tropical land of Indonesia determine by several factors, which are: days after fertilizing, fertilizer type and dosage, previous land use, growth phase of crops, sampling point and soil characteristic. The peak time was mostly influenced by crop type. Maize has the highest N2O daily fluxes with the range of 311.9 - 9651.6 ugN2O m-2day-1 and rubber plantation has the lowest with the range of 16.1 - 2270.7 ugN2O m-2day-1. Measurement of N2O from managed soil to determine annual emissions should be done at all crop types, soil types, considering crops growth phase and also high sampling frequency to prevent an over or underestimation.